Antibacterial Activity Screening of Bacillus sp. AM12 Associated with Mangrove Soil - Natania, Evellyne; Indraningrat, Anak Agung Gede; Widhidewi, Ni Wayan (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
The use of synthetic antibiotics to treat bacterial infections can trigger resistance of pathogenic bacteria to antibiotics. One effort to overcome this is to explore microorganisms that produce antibacterial compounds from nature. A previous study reported isolates of Bacillus sp. AM12 from mangrove soil displayed antibacterial potential based on preliminary screening of the perpendicular streak test. This study was designed to confirm the antibacterial potential of Bacillus sp. AM12 uses chemical solvent extraction. Bacillus sp. AM12 was fermented in 100 mL liquid ISP-2 sterile and shaken at 150 rpm for 7 days. The supernatant was filtered from the cell mass using Whatman paper and extracted using 100 mL of ethyl acetate solvent (1:1, v/v) twice. The filtrate was evaporated at 40ºC until a thick, clear yellowish colored extract was obtained. The thick extract was tested for antibacterial activity using the Kirby-Bauer method against two Gram positive and two Gram negative bacterial targets. Antibacterial screening showed moderate diameter zone of inhibition of 6.72 ± 0.21 mm, 6.82 ± 0.15 mm, and 6.62 ± 0.21 mm against Staphylococcus aureus ATCC 25923, Streptococcus mutans FNCC 0405, and Klebsiella pneumoniae ATCC 70060, respectively. However, no antibacterial activity was observed against Escherichia coli ATCC 25922. Analysis of the chemical composition of ethyl acetate crude extracts using GC-MS has detected 10 different compounds, in which the 3 most dominant antibacterial compounds were Benzene, 1,2,4-Trimethyl-, Benzene, 1-ethyl-2-methyl- and 2-butoxyethyl acetate. In general, these results provide an initial description of Bacillus sp. AM12 is a potential of antibacterial producer.